Validation of Nanopore long-read sequencing to resolve RPGR ORF15 genotypes in individuals with X-linked retinitis pigmentosa - Vaché, Christel; Faugère, Valérie; Baux, David; Mansard, Luke; Van Goethem, Charles; Dhaenens, Claire-Marie; Grunewald, Olivier; Audo, Isabelle; Zeitz, Christina; Meunier, Isabelle; Bocquet, Béatrice; Cossée, Mireille; et al. (European journal of human genetics : EJHG, 2025)
X-linked retinitis pigmentosa (XLRP) is characterized by progressive vision loss leading to legal blindness in males and a broad severity spectrum in carrier females. Pathogenic alterations of the retinitis pigmentosa GTPase regulator gene ( RPGR ) are responsible for over 70% of XLRP cases. In the retina, the RPGR ORF15 transcript includes a terminal exon, called ORF15, that is altered in the large majority of RPGR -XLRP cases. Unfortunately, due to its highly repetitive sequence, ORF15 represents a considerable challenge in terms of sequencing for molecular diagnostic laboratories. However, in a recent preliminary work Yahya et al. reported a long-read sequencing approach seeming promising. Here, the aim of the study was to validate and integrate this new sequencing strategy in a routine screening workflow. For that purpose, we performed a masked test on 52 genomic DNA samples from male and female individuals carrying 32 different pathogenic ORF15 variations including 20 located in the highly repetitive region of the exon. For the latter, we have obtained a detection rate of 80-85% in males and 60-80% in females after bioinformatic analyses. These numbers raised to 100% for both status after adding a complementary visual inspection of ORF15 long-reads. In accordance with these results, and considering the frequency of ORF15 pathogenic variations in XLRP, we suggest that a long-read screening of ORF15 should be systematically considered before any other sequencing approach in subjects with a diagnosis compatible with XLRP.